Monitoring health as a condition of introduction of the individual health program of schoolchild - Shahnenko V.I (Kharkov National Pedagogical University, 2012)
The purpose of the article is an attempt to conduct an analysis and comparison of the State standard of base and complete universal middle education with an operating on-line tutorial «Bases of health». The features of on-line tutorial for the 5-9th classes of general educational establishments are considered. Directions of increase efficiency of teaching of bases of health are recommended through introduction of monitoring of health on author «Passport of health». It contains sections which represent the social, spiritual, psychical and physical constituent of health. It is recommended to self-examination and analysis of results of control of individual health of students level to attract the teachers of bases of health, physical culture, medical staff of school, class leader and parents. On the basis of the last students the individual health program, which foresees the measures of maintenance of normal health or his improvement level, prophylaxis and correction of harmful habits, is developed.